Prevalence and pattern of permanent tooth agenesis among multiracial orthodontic patients in Malaysia - Zakaria Nor Nadia; Kamarudin Yasmin; Seong Lim Ghee; Sulaiman Nur Shahirra; Atirah Anuar Siti Aisyah (Sciendo, 2021)
Objective: To determine the prevalence and pattern of hypodontia among multiracial orthodontic patients in Malaysia.